Pengaruh Transformational Leadership dan Budaya Organisasi Terhadap Kinerja Karyawan Melaui Stres Kerja pada Dealer Wuling Arista Jayakarta - Raissa Arham Delyuzar; Astriyani Sandya Paramita; Achmad Zawawi; Farah Meutia Yosli (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
This research aims to determine the effect of transformational leadership (X1), organizational culture (X2) on employee performance (Y) with work stress (Z) as an intervening variable. The research was carried out by distributing questionnaires to 30 samples. The type of research used in this study is quantitative causality with a structural equation model (SEM) research method based on partial least square (PLS). The instrument validity test shows that each statement item has a product moment correlation coefficient value greater than r table, so it can be declared valid, then the instrument reliability test shows that the Cronbach alpha value for each instrument has a value > 0.70 so it can be stated reliable. The research results show that Transformational leadership (X1) has a positive and significant effect on employee performance (Y), organizational culture (X2) has a positive and significant effect on employee performance (Y), Transformational leadership (X1) has a negative and significant effect on stress work (Z), Organizational culture (X2) has a negative and significant effect on work stress (Z), Work stress (Z) has a negative and significant effect on employee performance (Y), Transformational leadership (X1) has a positive and significant effect on employee performance (Y) through work stress (Z), organizational culture (X2) has no effect on employee performance (Y) through work stress (Z).